Minat, Aspirasi Kerjaya dan Sikap Terhadap Mata Pelajaran Rekaan dan Jahitan Pakaian dalam Kalangan Murid - Kamis, Arasinah (2009)

(untitled)
The study is to explore the career, identify career aspirations, factors which determine attitude of students’ towards the RJP subject and career aspirations. It is also to see the difference in attitude of students towards this subject based on career aspirations and based on their parents’ level of education and occupation. A quantitative survey was carried out among 291 form four students taking RJP subject. Respondents were chosen using a cluster sampling method. Chi-square and ANOVA tests were used to see the relationship and differences between the variables being studied. Level of significance was at p< 0.05. Results show students have career aspirations parallel to the subject they are learning. There is a significant relationship between parents’ factor, [ χ² (6, N=285)=24.542, p=.000, Cramer’s V=.207 ] with respondents career aspiration; between counseling teacher, [ χ² (6, N=288)=20.21, p= .003, Cramer’s V=.187 ] with respondents career aspirations. There is no significant relationship between peers [ χ² (6, N=287)=5.67, p=.458, Cramer’s V=.100 ] with career aspirations of students taking RJP. The findings show those with career aspiration related to RJP have positive attitude towards RJP subject as compared to those with career aspiration not related to RJP F(2,285)=15.77, p≤.05. There is a significant difference between student’s attitude towards RJP based on mother’s occupation, F(8,282)=2.54, p≤.05. However, the result also show there is no significance difference between students attitude towards RJP based on mother’s level of education, F(4,286)=1.49, p≥.05, father’s level of education F(4,286)=.74, p≥.05 and father’s occupation, F(8,282)=0.63, p≥.05. On the whole, students place interest in the Social field as priority and Artistic field as their next area of interest. As such a continuous effort is deemed necessary to develop interest, career aspiration and attitude towards RJP among student enrolled in this subject. This is to enable them to develop interest and career aspiration relevant to RJP.